ANALISIS MOTIVASI DAN KEPUASAN BELAJAR SISWA DALAM PENERAPAN APLIKASI STATISTIK BERDASARKAN PERBEDAAN GENDER - faradiba Jabnabillah; Sasa Ani Arnomo; Lala Intan Komalasari; Widya Reza; Uzlah Sufyana (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2026)
The purpose of this study was to describe students' learning motivation and learning satisfaction in mathematics lessons by implementing statistical applications based on gender. using the Independent Sample T Test which is a test of differences between 2 unpaired groups. The location of this study was at SMA N 21. The subjects in this study were 30 grade XII students of Batam. The results of this study indicate that the use of statistical applications in learning does not cause differences in motivation and learning satisfaction between male and female students. Both groups showed similar responses to the application, both in terms of enthusiasm for learning and satisfaction with its features and benefits. This indicates that statistical applications are gender-neutral learning media, and can be used inclusively and fairly to support the effectiveness of learning for all students regardless of gender differences.